Utilization of investment casting shell waste in the production of cordierite-mullite-zircon composites for radiation shielding: The influence of La2O3 additive - ARTIR, RECEP (My University, 2023)
Cordierite-mullite-zircon ceramic composites were produced via reaction sintering of investment casting shell waste, Al2O3, and MgO at 1350 °C. The influence of La2O3 addition on the crystalline phase composition, microstructure, densification behavior, mechanical strength, and radiation shielding capabilities of the cordierite-mullite-zircon composites has been investigated. The X-ray diffraction (XRD) analysis confirmed the successful synthesis of cordierite-mullite-zircon composites with up to 5 wt% La2O3 additive content. However, a higher La2O3 content, exceeding 7 wt% resulted in cordierite decomposition. Furthermore, the addition of La2O3 significantly enhanced the densification behavior and microstructural development, leading to improved flexural strength and enhanced shielding against fast neutron and gamma radiation. This research suggests the potential of the fabricated ceramic composites derived from investment casting shell waste for applications in radiation shielding.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Other; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; KİMYA, UYGULAMALI; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; PHYSICS; MATERIALS SCIENCE, CERAMICS; CHEMISTRY, APPLIED; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; PHYSICS, CONDENSED MATTER; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Seramik ve Kompozitler; Proses Kimyası ve Teknolojisi; Yüzeyler, Kaplamalar ve Filmler; Malzeme Kimyası; Electronic, Optical and Magnetic Materials; Physical Sciences; Ceramics and Composites; Process Chemistry and Technology; Surfaces, Coatings and Films; Materials Chemistry